Evaluation of the E-Kinerja Application Implementation Policy at the Pamong Praja Police Unit Office of Kuningan District - Zulvie, Syifha (International Journal Labs, 2023)
The delegation of authority from the Central Government to Regional Governments plays a crucial role in expediting Bureaucratic Reform. One facet of this reform is the adoption of the E-Kinerja application across all Regional Work Units, prompted by employees deviating from their assigned duties and functions. Consequently, the work outcomes lack effectiveness, efficiency, transparency, and accountability. This research aims to assess the E-Kinerja application's implementation at the Kuningan Regency Civil Service Police Unit Office, identifying supporting and hindering factors and exploring strategies to overcome obstacles. Utilizing a case study method with a descriptive qualitative approach, key informants, including the Head of the Kuningan Regency Civil Service Police Unit, and supporting informants from various State Civil Apparatus, were interviewed. Findings indicate that some dimensions, such as Capability (Timeliness), Efficiency (Policy Process Efforts), Responsiveness (Apparatus and Leader Response), and Accuracy (Impact for the Agency and Government), are relatively optimal. However, certain dimensions, including Effectiveness (Ability), Efficiency (Policy Implementation Process), Adequacy (Human and Non-Human Resources), and Equity (Goal Achievement and Transparency), fall short of optimal performance. Understanding the extent of the E-Kinerja application's implementation at the Kuningan Regency Civil Service Police Unit Office is crucial for refining the reform process. Addressing deficiencies in the identified dimensions will be instrumental in enhancing the overall effectiveness and efficiency of bureaucratic functions, aligning with the broader objectives of Bureaucratic Reform.